Religiosity and Gender Dynamics in Executive Leadership: Impact on CEO Appointments and Pay Disparities - Bouckenooghe, Dave (Journal of business ethics, 2026)
In our study, we investigated the influence of local religiosity on two key aspects of corporate leadership dynamics: the likelihood of appointing female CEOs during transition periods and the connection between local religiosity and female CEO compensation. Considering the patriarchal underpinnings common to major religions which often support gender stratification and justify male hierarchical dominance, we anticipated a negative relationship between local religiosity and both the appointment and remuneration of female CEOs. However, our findings based on 2936 data points collected from multiple secondary data sources (e.g., PEW research center, EXECUCOMP, COMPUSTAT, IIS, CSRP) showed no significant relationship between local religiosity and the likelihood of hiring female CEOs. Additionally, our analysis, utilizing both longitudinal data from U.S.-listed firms from 1998 until 2021 (N = 25,826) and a propensity-scored matched sample (N = 1778) revealed that local religiosity has a positive and significant association with female CEO remuneration levels. These findings suggest that a premium might be paid for female CEOs breaking through the glass ceiling in highly religious states.